Factors of Competencies on Client Project Performance in a Public Transportation Company - Devina, Reta Sandra; Utomo, Christiono (IPTEK Journal of Proceedings Series, 2020)
In terms of producing good performance during company activities, an employee must have an ability/competency to carry out the assigned tasks according to their main tasks and functions. However, in its implementation, not all companies place their employees in their suitable positions/positions that are well-fitted with their capabilities/competencies. In the project client company, there is an allegation that the lack of competencies by their company employees is the cause of delays, poor quality, and the occurrence of disputes during the project cycle which causes the poor performance of a project. This paper reports several competency factors on client employees that affect individual client project performance in PT. K. The research sample of this study are employees of PT. K. Data collection using a questionnaire, the data on the questionnaire is analyzed using factor analysis. The results of this research resulted in 8 individual competencies that affect the performance of employees of PT. K formed in 2 factors. Factor 1 is a basic competency on individual characteristics consisting of technical/theoretical knowledge, procedural knowledge, willingness to establish good relations, psychomotor skills, job specific skills, tacit knowledge, and understanding of interaction and conflict objectives. In factor 2 of the top-level competence on the development of individuals, there are critical and creative thinking